Open, Laparoscopic, and Robotic Approaches for Inguinal Hernia Repair: A Comprehensive Review - Skiba, Jakub; Skiba, Zuzanna; Tylczyńska, Kinga; Tylczyńska, Natalia; Kowalik, Kinga; Michalska, Maria; Zielińska, Aleksandra; Szypulski, Szymon; Iwaniuk, Sebastian; Maciejewski, Ignacy (Quality in Sport, 2025)
Introduction and Purpose Inguinal hernia is one of the most common surgical conditions, affecting 27% of men and 3% of women over a lifetime. The mainstay of treatment is surgical repair, which prevents complications such as strangulation and bowel obstruction. This study aims to provide a comprehensive review of inguinal hernia pathophysiology, risk factors, diagnostic strategies, and treatment options, focusing on open, laparoscopic, and robotic repair techniques. Description of State of Knowledge The development of inguinal hernias is associated with connective tissue abnormalities, with studies showing an increased ratio of type III to type I collagen. Diagnosis relies primarily on clinical examination, with imaging techniques such as ultrasonography and MRI used in complex cases. Lichtenstein repair remains the standard open approach, offering low recurrence rates, while laparoscopic techniques (TAPP, TEP) are preferred for bilateral and recurrent hernias due to faster recovery and reduced chronic pain. Robotic-assisted repair provides enhanced precision and ergonomics, but current evidence shows no significant clinical advantage over laparoscopy, with higher costs and longer operative times. Conclusions Surgical repair is the gold standard for inguinal hernia treatment, with the choice of technique depending on patient factors, hernia characteristics, and surgical expertise. Lichtenstein repair remains the preferred open approach, while laparoscopic techniques (TAPP, TEP) are recommended for bilateral and recurrent cases due to their faster recovery and lower risk of chronic pain.